Arizona Hospital Discharge and Emergency Department Database: Implications for Occupational Health Surveillance. Issue 4 (April 2017) - Harber, Philip; Ha, Jennifer; Roach, Matthew
Abstract : Objectives: The objective of the project was to identify trends in emergency department visits and inpatient admissions for occupational injury and disease frequency and describe the financial impact from specific clinical groups known to have occupational risk factors. Methods: Workers compensation cases among 19 million records in the Arizona statewide hospital discharge database (HDD) were assessed for seven clinical groups from 2008 to 2014, including back, cardiac, carpal tunnel syndrome, heat-related, psychiatric, pulmonary, and trauma. Results: Cases with cardiac, psychiatric, and pulmonary diagnoses were both frequent and expensive. Although incidence was generally stable, charges per case rose significantly over the time period. Implications: Inpatient and emergency department records provide valuable data that complement other surveillance approaches for both occupational illnesses and injuries. Tracking charge as well as incidence data is useful. Abstract : Supplemental Digital Content is available in the text